(untitled) (Research, Society and Development, 2023)
This study aims to evaluate the muscle strength, functionality and length of tracheostomized patients’ stay by prolonged ventilation due to COVID-19 disease in an adult intensive therapy unit. It is a quantitative and retrospective research, through hospitalized patients’ medical records in a period of march 2020 to october 2020 of both genders, aged between 16 to 90 years approved by the research ethics committee. It was used a questionnaire created by the authors themselves that includes: muscle strength, functionality and length of stay in the (ICU) and it achieved successful decannulation still in the critical unit. It was statistically analized through the software IBM SPSS statistics, version 23. It was used 43 medical records where 27 individuals discharged from intensive care units and 16 progressed to death. It was observed that when compared the total time of mechanical ventilation with the functionality outcome there was no statistically significant difference (p>0,05). The shortest stay of VM on days ocurred for those who were bedridden or position change (27 _+ 9,4 days) and the longest stay was for those who were sitting out of bed with ability to cooperate (44 -+ 9,9 days) . Similarly it happened with dynamometry there was no positive correlation, however, the length of stay for those who achieved success of decannulation was 9,53 days (SD ± 3,65 days) well below the most studies have already published with the same sample.